Single-center experience with intraprocedural cleansing system to improve inadequate bowel preparation during colonoscopy - Herman, Tessa; Wongjarupong, Nicha; Wilson, Natalie; Megna, Bryant; Are, Vijay; Westanmo, Anders; Lou, Susan; Bilal, Mohammad; Hanson, Brian J (Endoscopy International Open, 2024)
Inadequate bowel preparation is common despite various preprocedure interventions. There is a need for an intervention at the time of colonoscopy to combat poor preparation. In this retrospective, observational study of 46 patients, we evaluated the clinical efficacy and feasibility of implementing the third generation of the Pure-Vu EVS System, a US Food and Drug Administration-cleared over-the-scope-based intraprocedural cleansing device, into our practice at the Minneapolis VA Medical Center (Minneapolis, Minnesota, United States). To study clinical efficacy, we measured bowel preparation adequacy before and after using the device, as measured by the Boston Bowel Preparation Score, and reviewed colonoscopy surveillance interval recommendations. Technical success and feasibility of using the device were measured by procedure success rates and duration. We found that BBPS scores increased from 4.4 to 7.9 when using the device. Technical success was achieved 78.3% of the time (36/46 cases). Median colonoscopy duration was 46 minutes, although there was a trend toward shorter procedures over time. This is the first clinical evaluation of the third generation of an intraprocedural cleansing device. We found the device efficacious and easy to use with low procedure failure rates, but it does come with a learning curve. We suspect that adoption of this device mutually will benefit patients and health systems with the potential to improve resource utilization.
Keywords: Quality and logistical aspects; Quality management; Endoscopy Lower GI Tract; Polyps / adenomas / ...; CRC screening